Feasibility of laparoscopic enucleation for hemangioma in special hepatic segments - Li, Huixing; Duan, Xuhong; Wu, Zhenyu; Qin, Yugang (Frontiers in Surgery, 2023)
Background and Aim: To evaluate the safety and efficacy of laparoscopic enuclearion for liver hemangioma in special hepatic segment. Methods: We retrospectively reviewed 58 patients who underwent laparoscopic surgery for hepatic hemangioma at a single center from January 2016 to January 2022. Patients were categorized into the special location group(SLG) and the normal location group(NLG) according to the location of the hemangioma. General data, intraoperative and postoperative outcomes, and postoperative complications in the two groups were compared and analyzed. Results: There were no significant differences in age (51.8±4.7 vs. 53.3±5.8 years, p=0.288), gender (p=0.331), BMI (25.3±2.8 vs. 24.4±2.1, p=0.168), the maximum diameter of hemangioma (11.7±2.3 vs. 12.8±5.4 cm, p=0.330 ), ASA risk grading (p=0.615), or comorbidities (p>0.05 ) between the two groups. The operation time (258.4±49.2 vs. 186.2±51.8 min, p<0.001), intraoperative blood loss (466.7±235.7 vs. 259.3±92.6 ml, p<0.001) , and intraoperative blood transfusion rate (29.6% vs. 6.5%, p=0.047) were significantly higher in the SLG. The rate of conversion to laparotomy(14.8% vs. 0.0%, p=0.089) was higher in the SLG, but there was no significant difference. In addition, the exhaust time(3.8±1.4 vs. 2.9±0.8 days, p=0.03) and postoperative hospital stay (11.5±3.4 vs. 7.3±2.6 days, p<0.01) were significantly shorter in the NLG. The postoperative complications were comparable between the two groups , and there were no perioperative deaths. Conclusions: Laparoscopic enucleation of hemangioma in special hepatic segments is difficult and has a critically risk of massive bleeding during surgery. Meanwhile, it is also safe, feasible and effective. Grasping indications of laparoscopic surgery, good preoperative planning, skilled laparoscopic technique and tacit teamwork are significant factors for the success of this surgery.